Analysis of Antifungal Activity of Artocarpus camansi Leaf Extract Against Malassezia furfur: An In Vitro Experimental Study - Megan Seelena; Renata Prameswari; Verna Biutifasari; Stefanus Djoni Husodo (Universitas Muhammadiyah Surabaya, 2026)
A lipophilic fungus, Malassezia furfur, is responsible for several skin diseases. The conventional treatment is ketoconazole, but concerns about adverse effects and resistance have prompted the search for natural alternatives such as Artocarpus camansi, whose effectiveness remains poorly understood despite its bioactive flavonoid and steroid content. The purpose of this study was to assess the in vitro antifungal activity of leaf extract from Artocarpus camansi against Malassezia furfur at doses of 25%, 50%, 75%, and 100%. This laboratory experimental study employed the disc diffusion method. Kruskal-Wallis and Mann-Whitney U tests were used to assess and statistically analyze the inhibition zones of the therapy Artocarpus camansi leaf extract at doses of 25%, 50%, 75%, and 100%, with four replications each. The mean inhibition zone for the positive control was 9.53 mm. On the other hand, no inhibitory zone (6.00 mm diameter) was formed by any of the Artocopus camanci extract doses or the negative control. There were no significant differences between the extract concentrations (p>0.05), but there was a significant difference between the positive control and all extract groups (p=0.014). In conclusion, at the tested concentrations, Artocarpus camansi leaf extract shows no antifungal activity against Malassezia furfur, whereas Ketoconazole remains a useful inhibitor.